Functional Composition, Nutritional Properties, and Biological Activities of Moroccan Spirulina Microalga - Rajaa Seghiri; Mourad Kharbach; Azzouz Essamri (Journal of Food Quality)
The present study aimed to characterize the nutraceutical properties and the antimicrobial effect of Moroccan Spirulina (Arthrospira platensis). The nutritional composition was evaluated, including water content, crude protein, total carbohydrates, lipids, phenolic composition, macro- and micromineral content, fiber content, and energy value. Then, the microbiological analysis and antioxidant activity were measured. The antimicrobial activity was evaluated using the minimum inhibitory concentration method on bacteria and fungi. Moroccan Spirulina contained a large amount of protein (76.65 ± 0.15%), followed by carbohydrates (6.46 ± 0.32%), minerals (20.91 ± 0.88%), crude fiber (4.07 ± 1.42%), lipids (2.45 ± 0.82%), ash (14.56 ± 0.74), and twenty phenolic acids being identified and quantified. Moreover, flavonoid and phenolic contents were present at 15.60 ± 2.74 mg RE/g dw and 4.19 ± 0.21 mg GAE/g dw, respectively. Microbiological risk assessment indicated that this product is safe to be consumed as a human food product. The antioxidant activity was higher in the methanolic fraction (23 mg TE/g dw) (DPPH).